Pengaruh Tax Planning Dan Beban Pajak Tangguhan Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2021) - Gurning, Dewi Lasmaria; Oktavianna, Rakhmawati (Jurnal Pajak Vokasi (JUPASI), 2024)
This study aims to empirically test and prove the effect of Tax Planning and Deferred Tax Expenses on Company Value. This research was conducted on food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The type of research used is quantitative with purposive sampling in sampling. The population in this study is the annual financial reports from 2017 to 2021, namely 65 are the sample in this study. Statistical testing uses Eviews 9. The results of this study show that tax planning and deferred tax expenses on company value in food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange for the 2017-2021 period simultaneously or jointly have an effect on company value. Partial Research Tax Planning Has no effect and is on firm value and Deferred Tax Expenses have a positive and significant effect on firm value.